Association between SARS-CoV-2 infection and the physical fitness of young-adult cadets: a retrospective case–control study. Issue 12 (14th December 2022) - Peretz, Lidor; Grossman, Akiva; Saeed, Salih J; Appleboim-Refael, Talia; Zloof, Yair; Friedensohn, Limor; Shapira, Shachar; Shlaifer, Amir; Grotto, Itamar
Abstract : Objectives: To determine the association of symptomatic and asymptomatic mild COVID-19 and the SARS-CoV-2 viral load with the physical fitness of army cadets. Design: A retrospective case–control study. Setting: Officers' Training School of the Israel Defense Forces. Participants: The study included all cadets (age, 20.22±1.17 years) in the combatant (n=597; 514 males, 83 females; 33 infected, all males) and non-combatant (n=611; 238 males, 373 females; 91 infected, 57 females, 34 males) training courses between 1 August 2020 and 28 February 2021. COVID-19 outbreaks occurred in September 2020 (non-combatants) and January 2021(combatants). Primary and secondary outcome measures: The primary outcome measures were the aerobic (3000 m race) and anaerobic (combatant/non-combatant-specific) physical fitness mean score differences (MSDs) between the start and end of the respective training courses in infected and non-infected cadets. Secondary outcome measures included aerobic MSD associations with various COVID-19 symptoms and SARS-CoV-2 viral loads. Results: SARS-CoV-2 infection led to declined non-combatant and combatant aerobic fitness MSD (14.53±47.80 vs –19.19±60.89 s; p<0.001 and –2.72±21.74 vs –23.63±30.92 s; p<0.001), but not anaerobic. The aerobic physical fitness MSD decreased in symptomatic cadets (14.69±44.87 s) and increased in asymptomatic cadets (–3.79±31.07 s), but the difference was statistically insignificant (p=0.07). Symptomatic cadets with fever (24.70±50.95 vs –0.37±33.87 s; p=0.008) and headache (21.85±43.17 vs 1.69±39.54 s; p=0.043) had more positive aerobic physical fitness MSD than asymptomatic cadets. The aerobic fitness decline was negatively associated with viral load assessed by the RNA-dependent RNA polymerase (n=61; r = –0.329; p=0.010), envelope (n=56; r = –0.385; p=0.002) and nucleus (n=65; r = –0.340; p=0.010) genes. Conclusions: SARS-CoV-2 infection was associated with a lingering decline in aerobic, but not anaerobic, fitness in symptomatic and asymptomatic young adults, suggesting possible directions for individualised symptom-dependent and severity-dependent rehabilitation plans' optimisation.